STANDARD OPERATING PROCEDURES OF THE INTEGRATED DESIGN AND BUILD TOLL ROAD CONSTRUCTION IN INDONESIA - Muljono, Slamet; Siahaan, Hardy P. (Jurnal HPJI, 2018)
Abstract The government is striving for planned toll roads to be realized so as to increase connectivity, competitiveness and lower logistics costs. In turn, the toll road can be the backbone that supports the growth of the national economy as well as the equitable distribution of development. Based on the review of Indonesia Toll Road Authority of the Ministry of Public Works and Housing in 2017, it is projected that Indonesia will have an additional 1,851 km of new toll roads by the end of 2019. The additional projection of the new toll road exceeds the targets set in the Strategic Plan of the Ministry of Public Works and Housing 2015-2019 as long as 1,060 km. The additional projection of new toll roads is possible besides the acceleration of land acquisition process through bailout fund by Toll Road Business Entity also introduced system delivery innovation by implementing Integrated Design and Build Constructions. Therefore, it needs to be equipped with Standard Operating Procedures for the Integrated Construction Design and Build on Toll Road Project in Indonesia. Keywords: toll road, standard operating procedures, toll road authority, toll road business entity  Abstrak Pemerintah sedang mengupayakan ruas-ruas jalan tol yang direncanakan untuk direalisasikan sehingga dapat meningkatkan konektivitas, daya saing, dan menurunkan biaya logistik. Pada gilirannya, jalan tol dapat menjadi tulang punggung yang mendukung pertumbuhan ekonomi nasional serta pemerataan pembangunan. Berdasarkan kajian Badan Pengatur Jalan Tol, Kementerian Pekerjaan Umum dan Perumahan Rakyat, pada 2017, diproyeksikan bahwa Indonesia akan memiliki tambahan 1.851 km jalan tol baru pada akhir 2019. Proyeksi tambahan jalan tol baru ini melebihi target yang ditetapkan dalam Rencana Strategis Kementerian Pekerjaan Umum dan Perumahan Rakyat 2015-2019, yaitu  sepanjang 1.060 km. Proyeksi tambahan jalan tol baru dimungkinkan karena selain percepatan proses pembebasan tanah melalui dana talangan oleh Badan Usaha Jalan Tol juga diterapkannya sistem Design and Build Integrated Constructions. Karena itu diperlukan adanya Prosedur Operasi Standar untuk Integrated Design and Build Constructions untuk proyek-proyek jalan tol di Indonesia. Kata-kata kunci: jalan tol, prosedur operasi standar, badan pengatur jalan tol, badan usaha jalan tol